Sistema de navegação para atividades em campo – SNAC - Lamb, Juliano Rodrigo (2020)
The population growth observed in recent years indicates that the means of food production demand techniques to increase its production, regarding the agricultural and livestock sectors. In the agricultural area, Precision Agriculture (PA) stands out. This is an agricultural management process that considers areas with a possible heterogeneous behavior and investigates and treats each demand spatially located. This monitoring requires the collection of various pieces of information, ranging from climatic attributes, human elements and soil and plant factors. Among this diverse information, the soil is an important factor that can interfere in productivity, with problems such as compaction, or deficiency of some physical-chemical property, Therefore, analysis is necessary to measure these needs. The use of mobile devices, such as cell phones and tablets in agricultural activities is still incipient, however, due to the processing capacity, mobility, and location, they can be used in various field activities, such as plot demarcation, data recording field, as well as the location of sample points, in the context of PA. These devices, besides costing less than commercial low-precision GNSS equipment used for this purpose, have available features and resources that make them more attractive to purchase. This work aimed to develop and validate an application for mobile devices, which allows the import and location of sampling points for data collection. The application was developed using the JAVA language for devices with Android operating systems. The software was tested in the field with the use of a smartphone due to its practicality and available features, as well as its accuracy concerning geolocation. It was found that the use of the application allowed the work to be carried out in the field, which can be used in data collection activities in the context of PA. In the point location, the tests with the equipment showed an average accuracy close to 1m, with precision equivalent to a dedicated GNSS device, demonstrating that it can be used in agricultural activities when required accuracy is close to this value. The results also suggest that the accuracy is superior when the tests are carried out in the morning.